CONFISCATION OF PROPERTY IN THE POLICY OF CRIME FIGHTING IN OUR COUNTRY (Scientific journal of the Fergana State University, 2023)
This article deals with the concept of confiscation of property, the legal basis and significance of the act of confiscation of property in criminal procedure legislation, as well as issues of improving the existing legislation in this sphere.